Faking global health. Issue 4 (8th August 2019) - Erikson, Susan
ABSTRACT: Globally, human health is improving. Aggregate world health data indicate enormous improvement over the last 100 years. Life expectancy, vaccination, and sanitation rates are higher. Rates of infectious disease, HIV/AIDS, child and maternal mortality are lower. These gains have all been accomplished during a time when governments orchestrated, or aspired to provide, albeit often imperfectly, the systemizations of health care. Now austerity and privatization campaigns shape health services worldwide, and we witness a massive ideological shift in approaches to the world's wickedest health problems: Public health endeavors must 'show return on investment.' This commentary takes up activities in three health domains where effort goes into the appearance of global health prowess and accomplishment: health security; health innovation; and health finance. Pseudo global health, as an analytic, helps us take measure of the in-between phenomenon between real and fake accomplishment, success and failure, improved health outcomes and continued suffering. I show: 1) how global health security documents sometimes serve as 'alibis' – that is, contrivances offered to intimate local readiness or safety despite their actual absence; 2) how global health innovation influencers often privilege tech-fixes developed far removed from real-time people, places, and practices; and 3) how global health finance has already evolved in ways that makes suffering profitable. The examples are meant to enlighten rather than depress and are offered with the hope that critical analyses using the pseudo health concept as an analytic prompt new strategies for sustainable changes rather than merely their appearance.